FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEMAUAN MEMBAYAR PAJAK WPOP DI LINGKUNGAN UNIVERSITAS NEGERI SURABAYA - PUTRI VIOLITA, POPY (Jurnal Akuntansi AKUNESA, 2015)
This study aimed to determine the effect of taxpayer awareness, knowledge and understanding of taxation laws, a positive perception of the effectiveness of the tax system, taxpayer confidence level of the legal system and government, quality of service and tax modernization on willingness to pay tax in State University of Surabaya. The reseacrh use quantitative research methods with questionnaire.The population is taxpayer which lecturer and educator in State University of Surabaya. Sampling was done by the method of convenience sampling with 305 sample minimum that determined of slovin formula. Model of data analysis used in this study was a multiple linear regression analysis. The result shows that the partial results of hypothesis testing (t-test) proves that the variable of positive perception of the effectiveness of the tax system and taxpayer confidence level of the legal system and government has not effect on willingness to pay tax. Keywords: taxpayer awareness, knowledge and understanding, quality of service, tax modernization, wilingness to pay tax.